Pemberdayaan Pemuda Putus Sekolah melalui Pelatihan Kecakapan Hidup Montir Sepeda Motor di Panti Sosial Bina Remaja Taruna Jaya Kecamatan Tebet Kota Jakarta Selatan - Dadan Darmawan; Rosandro Gabriel; Sholih Sholih (MASALIQ, 2025)
The issue of school dropout youth in urban areas such as South Jakarta presents a significant social challenge, where low skills and limited employment access hinder their independence. This study aims to identify the stages of youth empowerment through life skills training and to assess the impact of the training on participants’ job readiness and self-reliance. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The data sources included seven informants: the training coordinator, a motorcycle mechanic instructor, and four dropout youths participating in the training. The findings reveal that the empowerment process consists of preparation (formation of personnel and facilities), assessment (needs identification through psychological testing and socialization), alternative planning (determining duration and collaborating with external institutions), action formulation (program design), implementation (theoretical and practical instruction), evaluation (monthly monitoring), and termination (participants gain employment and income). Motorcycle mechanic training proved to positively contribute to enhancing technical skills, self-confidence, and motivation for economic independence among participants. This program serves as a practical and relevant alternative solution to equip school dropout youth with life skills aligned with labor market demands.